Biofuels: in search of green gold - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
Soaring oil prices have rekindled an interest in plant-based biofuels. Sugarcane, cassava, sorghum or jatropha: in ACP countries, testing is forging full speed ahead to find the best source...